The mind of Germany : - Kohn, Hans (Macmillan & Co Ltd, 1962)
The history of modern Germany is a study in national suicide. The enormous prestige won by the Germans, especially in scholarship and music, literature and philosophy, was deliberately destroyed by the Germans themselves. Now that Western world, we cannot help asking why this sucide took place.